International entrepreneurship (Advances in entrepreneurship, firm emergence and growth, 2005)
This eighth volume in the series Advances in Entrepreneurship, Firm Emergence and Growth focuses on international entrepreneurship. We are fortunate to draw on scholars both new to the field as well as some of those who founded this unique speciality. Topics include: international social capital, technology sharing and foreign market learning in internationalizing entrepreneurial firms; export performance of new ventures in the Finnish and Indian Software industries; institutional and economic influences on Internet adoption and accelerated firm internationalization; the role of strategic adaptation and networking capabilities in explaining new venture growth in international markets; illustration of the small world phenomenon to discuss network analysis tools that can be applied to international entrepreneurship research; an institutional perspective and cross-national comparison of incubated firms; a discussion of the means to achieving excellence in international entrepreneurship education; the export intensity of venture capital backed companies; and capability development, learning and growth in international entrepreneurial firms within China